2020
DOI: 10.1093/ageing/afaa167
|View full text |Cite
|
Sign up to set email alerts
|

Comparing associations between frailty and mortality in hospitalised older adults with or without COVID-19 infection: a retrospective observational study using electronic health records

Abstract: Background The aim of this study was to describe outcomes in hospitalised older people with different levels of frailty and COVID-19 infection. Methods We undertook a single centre, retrospective cohort study examining COVID-19 related mortality using Electronic Health Records, for older people (65 and over) with frailty, hospitalised with or without COVID-19 infection. Baseline covariates included demographics, Early Warning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
157
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(172 citation statements)
references
References 27 publications
14
157
0
1
Order By: Relevance
“…To date, most studies are describing mortality without reference to a contemporaneous non-COVID-19 population, which would obscure the interaction apparent in our data. In this respect, our findings are most consistent with comparable data from Leicester which also show no association between frailty and mortality in COVID-19 [15].…”
Section: Discussionsupporting
confidence: 91%
“…To date, most studies are describing mortality without reference to a contemporaneous non-COVID-19 population, which would obscure the interaction apparent in our data. In this respect, our findings are most consistent with comparable data from Leicester which also show no association between frailty and mortality in COVID-19 [15].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of frailty (CFS ≥ 5) in our study was high (66.9%), which was similar to recently published results from a cohort comparing non-COVID-19 older patients with COVID-19 patients [23]. These figures are high but unsurprising, given the unselected nature of our cohort who are hospitalised with COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…These values contrast with the prevalence of frailty in community-dwelling older people, where previous estimates have ranged from 9.9-13.6% (pooled estimates) [15], to 22.4% and 43.7% over the age of 65, and over the age of 85, respectively [16]. In a non-COVID-19 population, all-cause mortality in the severely frail was 33%, but was much higher in the COVID-19 group at 60% [23]. This implies that frailty is not the sole cause of mortality, rather a key factor for consideration, along with the acute illness [27].…”
Section: Discussionmentioning
confidence: 82%
“…A growing number of studies have investigated the association between frailty, frequently measured using the CFS in hospital settings, and mortality among patients, but findings remain inconclusive. While there is evidence that frailty may add to the risk prediction in hospitalized patients [16][17][18][19], some studies have observed weak [20,21], or All rights reserved. No reuse allowed without permission.…”
Section: International Statistical Classification Of Diseases and Relmentioning
confidence: 99%